Healthcare-associated infections: potential for prevention through vaccination - E. David G. McIntosh (SAGE Publishing, 2018)
The challenge of healthcare-associated infections is compounded by the higher incidence of resistant organisms and the decreasing utility of antimicrobial agents. Historic and current vaccines have already contributed to reductions in healthcare-associated infections, and future vaccines have the potential to reduce these infections further. Through examples of bacterial and viral vaccines, this review will attempt to chart the way forward.